Peningkatan Kualitas Hidup Bekerja pada Masyarakat Desa Sumber Melati Diski Kecamatan Sunggal Kabupaten Deli Serdang - Hasanuddin Hasanuddin; Retna Astuti Kuswardani; Sri Milfayetty; Abidah Ayu (Pelita Masyarakat, 2020)
Improving the quality of work life in the community, especially in Sumber Melati Diski Village, needs to be done. The purpose of this activity is to provide and strengthen the community to develop themselves and have the ability to cope with stress so that they can achieve a quality work life. The selection of partner locations is based on the needs of the community in Sumber Melati Village to alleviate the stress problem that is carried out through every community activity, both Posyandu, Perwiritan and others. The method is a workshop with creative art techniques. The capacity of the community is strengthened is to know the source of the problem, analyze, create and implement the design of problem alleviation, counseling and play therapy. The results of the mentoring show that people who solve problems with creative techniques can solve their problems personally and make decisions quickly. Furthermore, creative counseling that is carried out in groups can overcome emotional problems and minimize social problems. From this activity it was found that creative techniques in problem solving can minimize stress on the community which can effectively improve the quality of working life in the community of Sumber Melati Diski Village.